MEMBANGUN KEWIRAUSAHAAN MELALUI DIGITAL MARKETING DALAM DUNIA BISNIS DI DESA BANYU ASIH KABUPATEN BOGOR - Amalia Fauziah , Alma; Nurlaelatus Syufi , Siti; Fadilah , Hapid (Lembaga Penelitan dan Pengabdian Masyarakat Institut Agama Islam Sahid, 2025)
TThis research aims to empower the community, especially the young generation of Banyu Asih Village, in getting to know and build entrepreneurship through digital marketing in the business world. This type of research is qualitative research, the data collection techniques used in this study are carried out by observation and literature study. The literature sources used are secondary sources, such as journals, print and digital books, and other materials that remain relevant to the research topic. This research involved 69 students of SMPI and SMKI Qoryah Thoyyibah Al-Mugni. The data collection techniques used in this study were carried out by observation and literature study. The high enthusiasm of students shows that the material presented is relevant and interesting to the younger generation.